Long term evolution of soft tissue response in the fingers of high-level sport climbers: A cross-sectional 10 Year follow-up study. (November 2021) - Fröhlich, Stefan; Schweizer, Andreas; Reissner, Lisa; Pastor, Tatjana; Spörri, Jörg; Pastor, Torsten
Abstract: Background: Sport climbing induces physiological changes in the body of high-level climbers. In 2012, our study group demonstrated adaptions of elite climbers' soft tissues with thicker A2/A4-pulleys, flexor tendons and palmar plates compared to non-climbers. Objectives: To assess these adaptations over time we examined all 31 (follow up 100%) climbers that participated in that baseline study again using ultrasonography after a follow-up of 10 years. Main findings: (1) In climbers, a significant increase in A2 and A4-pulley and flexor tendon thickness over the last 10 years was observed (p < 0.001), while PIP&DIP palmar plate thickness remained unchanged (p > 0.05); (2) at 10-years follow-up, all soft tissue thickness parameters (incl. palmar plates) were still significantly larger in climbers than in age-matched controls (p < 0.05); (3) as for the association with anthropometrics and climbing performance/experience, a significant association of the current climber's soft tissue thickness could only be found between palmar plate and reached climbing level(p = 0.032) as well as climber's body weight(p = 0.004). Conclusion: An accumulation of repetitive climbing-related stress to the fingers of elite sport climbers over the career induces mechano-adaptation of the A2/A4-pulleys, flexor tendons and palmar plates. At later stages, there is a further significant increase in flexor tendon and pulley thickness, but not for palmar plate thickness. Highlights: Long term elite climbers show thicker A2/A4 pulleys, flexor tendons and palmar plates in their fingers compared to controls. Later, there is a further significant increase in flexor tendon and pulley thickness, but not for palmar plate thickness.